Availability of national policies, programmes, and survey-based coverage data to track nutrition interventions in South Asia - Neupane, Sumanta; Jangid, Manita; Scott, Samuel P.; Kim, Sunny S.; Murira, Zivai; Heidkamp, Rebecca; Carducci, Bianca; Menon, Purnima (Wiley, 2024)
Progress to improve nutrition among women, infants and children in South Asia has fallen behind the pace needed to meet established global targets. Renewed political commitment and monitoring of nutrition interventions are required to improve coverage and quality of care. Our study aimed to assess the availability of national nutrition policies, programmes, and coverage data of nutrition interventions for women, children, and adolescents in eight countries in South Asia. We reviewed relevant policy and programme documents, examined questionnaires used in the most recent rounds of 20 nationally representative surveys, and generated an evidence gap map on the availability of policies, programmes, and survey data to track progress on coverage of globally recommended nutrition interventions. Current policies and programmes in South Asian countries addressed almost all the recommended nutrition interventions targeted at women, children, and adolescents. There was a strong policy focus in all countries, except Maldives, on health system platforms such as antenatal and postnatal care and child growth and development. Survey data on nutrition intervention coverage was most available in India and Nepal, while Bangladesh and Bhutan had the least. Though countries in South Asia have committed to national nutrition policies and strategies, national surveys had substantial data gaps, precluding progress tracking of nutrition intervention coverage. Greater attention and effort are needed for multisectoral collaboration to promote and strengthen nutrition data systems.